Risk Factors for Failed Tracheal Intubation in Pediatric and Neonatal Critical Care Specialty Transport. (1st January 2015) - Smith, Kristen A.; Gothard, M. David; Schwartz, Hamilton P.; Giuliano, John S.; Forbes, Michael; Bigham, Michael T.
Abstract Objective. Nearly 200, 000 pediatric and neonatal transports occur in the United States each year with some patients requiring tracheal intubation. First-pass intubation rates in both pediatric and adult transport literature are variable as are the factors that influence intubation success. This study sought to determine risk factors for failed tracheal intubation in neonatal and pediatric transport. Methods. A retrospective chart review was performed over a 2.5-year period. Data were collected from a hospital-based neonatal/pediatric critical care transport team that transports 2, 500 patients annually, serving 12, 000 square miles. Patients were eligible if they were transported and tracheally intubated by the critical care transport team. Patients were categorized into two groups for data analysis: (1) no failed intubation attempts and (2) at least one failed intubation attempt. Data were tabulated using Epi Info Version 3.5.1 and analyzed using SPSSv17.0. Results. A total of 167 patients were eligible for enrollment and were cohorted by age (48% pediatric versus 52% neonatal). Neonates were more likely to require multiple attempts at intubation when compared to the pediatric population (69.6% versus 30.4%, p = 0.001). Use of benzodiazepines and neuromuscular blockade was associated with increased successful first attempt intubation rates (p = 0.001 and 0.008, respectively). Use of opiate premedication was not associated with first-attempt intubation success. The presence of comorbid condition(s) was associated with at least one failed intubation attempt (p = 0.006). Factors identified with increasing odds of at least one intubation failure included, neonatal patients (OR 3.01), tracheal tube size ≤ 2.5 mm (OR 3.78), use of an uncuffed tracheal tube (OR 6.85), and the presence of a comorbid conditions (OR 2.64). Conclusions. There were higher rates of tracheal intubation failure in transported neonates when compared to pediatric patients. This risk may be related to the lack of benzodiazepine and neuromuscular blocking agents used to facilitate intubation. The presence of a comorbid condition is associated with a higher risk of tracheal intubation failure.